The young Ibsen’s theatre aesthetics - a theatre of the old free and mountainous north - Andersen, Anette Storli (Nordlit, 2015)
The overall perspective of this article will be how drama as theatre, plays a part in the making of common worlds. I disagree with Benedict Anderson when he argues that the development of a printed national language was a basis for an imagined community and a condition for the modern nation state. When Ibsen and his contemporaries were fighting for a Norwegian theatre and theatre aesthetics in the 1850s and early 1860s, a written Norwegian language, which was distinctly different from written Danish, did not exist. In order to explain how the Norwegians could have a common imagined community before 1814 and the background for the young Ibsen’s theatre aesthetics, it is necessary to take a look at the theatre traditions Ibsen and his generation inherited – from, what is often referred to as the generation of 1814. It is also necessary to establish a perspective, which does not focus on written or printed language, but on theatre as human action. From 1850 to 1864 Ibsen was a prominent representative for a movement who wanted to develop a national theatre. The function of this national theatre was to be a mirror that could help the nation to correct itself, to strengthen the national self-consciousness. The theatre should be a place where the Norwegian people could experience an inner unity and an external demarcation of the nation. Ibsen participated in this national theatre project both as a theatre critic, as a playwright, as the author of prologues, epilogues and songs filled with national sentiment – and he was struggling for governmental support for the Norwegian theatre on this basis.